Characterization of Neoantigen Load Subgroups in Gynecologic and Breast Cancers - Zhu, Yue; Meng, Xiaowei; Ruan, Xinjia; Lu, Xiaofan; Yan, Fangrong; Wang, Fei (Frontiers in Bioengineering and Biotechnology, 2020)
Objective: Although gynecologic and breast (Pan-Gyn) cancers share a variety of similar characteristics, their response to immunotherapy is different. Immune checkpoint inhibitor (ICI) therapy is not effective in all patients, while neoantigen load (NAL) may be a predictive biomarker. However, the selection of NAL cut-off point and its predictive effect remain to be elucidated. Methods: We divided 812 Pan-Gyn cancer samples from the Cancer Genome Atlas (TCGA) into three groups based on 60% and 80% of their load percentile. We then correlated the identified neoantigen load subgroups with gene expression, somatic mutation, DNA methylation, and clinicopathological information. We also characterized each subgroup by distinct immune cells enrichment, PD-1 signaling and cytolytic activity. Finally, we predicted the response of each subgroup to chemotherapy and immunotherapy. Results: Across Pan-Gyn cancers, we identified 3 distinct neoantigen load subgroups. These subgroups showed difference in biological function, genetic information, clinical variables and immune infiltration. 80% was identified as a meaningful cut-off point for NAL. In all patients, higher NAL (top 20%) was associated with better overall survival as well as high immune infiltration and low intra-tumor heterogeneity. Furthermore, an interesting lncRNA named AC092580.4 was found, which was associated with two significantly different immune genes (CXCL9, CXCL13). Conclusions: Our novel findings provide further insights into the neoantigen load of Pan-Gyn cancers and may open up novel opportunities for their exploitation towards personalized treatment with immunotherapy.